Enamel apatite crystallinity significantly contributes to mammalian dental adaptations - Anna Kallistová (Nature Portfolio, 2018)
Abstract The monophyodont molar teeth, prismatic enamel and the complexity of enamel microarchitecture are regarded as essential dental apomorphies of mammals. As prominent background factors of feeding efficiency and individual longevity these characters are crucial components of mammalian adaptive dynamics. Little is known, however, to which degree these adaptations are influenced by the crystallographic properties of elementary hydroxyapatite crystallites, the only inorganic component of enamel. In a miniature pig where individual molars differ significantly in duration of their development and in enamel resistance to attrition stress, we found highly significant differences between the molars in the size of crystallites, amount of microstrain, crystallinity and in enamel stiffness and elasticity, all clearly scaled with the duration of tooth calcification. The same pattern was found also in red deer bearing different molar type. The results suggest that the prolongation of tooth development is associated with an increase of crystallinity, i.e. the atomic order of enamel hydroxyapatite, an obvious component of micromechanical property of mature enamel. This relation could contribute to prolongation of dental development, characteristic of mammals in general. The aspects of enamel crystallinity, omitted in previous studies on mammalian and vertebrate dental evolution, are to be taken in account in these topics.